Assessing type-2 diabetes risk based on the Indian diabetes risk score among adults aged 45 and above in India - Karthika Maniyara; Prakash Babu Kodali (Scientific Reports)
Abstract Millions of Indian adults are pre-diabetic with a greater risk of developing type-2 diabetes mellitus (T2DM). We conducted this study to assess the prevalence of type-2 diabetes risk among non-diabetic adults aged 45 years and above and identify the correlates for diabetes risk. We conducted a secondary analysis of Longitudinal Ageing Study in India (LASI) wave 1 data. A sample of 51,315 non-diabetic adults was extracted from LASI data and analysed. Type-2 diabetes risk was assessed based on the Indian Diabetes Risk Score (IDRS) by using four risk factor variables [i.e., (1) age of the respondent, (2) waist circumference, (3) family history of diabetes, and (4) physical activity]. A diabetes risk score of ≥ 60 was considered a high risk for diabetes. Descriptive statistics and multivariate analysis were conducted to assess the prevalence and correlates of diabetes risk respectively. About 41.2% had a high risk of diabetes. Among major Indian states, Kerala leads with 64.4% of its adults 45 years and above at high risk of diabetes. Obese level BMI (AOR  4.17; 95% CI 3.59–4.84), High cholesterol (AOR  1.51; 95% CI 1.22–1.87), History of heart disease and stroke (AOR  1.85; 95% CI 1.60–2.13), and males (AOR 1.25; 95% CI 1.16–1.34) had positive odds for high risk of diabetes. Individuals from scheduled tribes (AOR  0.85; 95% CI 0.76–0.96) had lower odds of diabetes risk. Obese individuals with a history of heart disease/stroke had a significantly higher (AOR  5.30; 95% CI 4.39–6.41) risk for diabetes. The findings suggest that it is essential to establish population-level interventions to tackle the modifiable risk factors for diabetes. Educational programs on diet and physical activity, creation of public spaces conducive to physical activity, promotion of fruit and vegetable intake, and discouragement of processed and ultra-processed diets can directly address inadequate physical activity and obesity, the two primary modifiable risk factors for type-2 diabetes. Additionally, strengthening health systems for early screening and management of diabetes and pre-diabetes is needed to prevent the diabetes epidemic.